2022
DOI: 10.5194/acp-22-6919-2022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics, sources, and formation pathways of organosulfur compounds in ambient aerosol in Guangzhou, South China

Abstract: Abstract. Organosulfur compounds (OrgSs), especially organosulfates, have been widely reported to be present in large quantities in particulate organic matter found in various atmospheric environments. Despite hundreds of organosulfates and their formation mechanisms being previously identified, a large fraction of OrgSs remain unexplained at the molecular level, and a better understanding of their formation pathways and critical environmental parameters is required to explain the variations in their concentra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 102 publications
0
28
0
Order By: Relevance
“…Figure a–c presents the distributions of carbon atom numbers in the molecular formula assignments. The majority of the CHOS and CHONS species have carbon atom numbers of C 4 –C 11 , which can be derived from a variety of biogenic precursors and anthropogenic aromatic hydrocarbons and long-chain alkanes. , The species with C 8 –C 10 were particularly predominant, which might be associated with the oxidation products of benzene, polycyclic aromatic hydrocarbons, long-chain alkanes, and monoterpenes . The number of the CHOS species with C 12 –C 19 was apparently increased during the haze episode, suggesting that the precursors such as long-chain alkanes and/or sesquiterpenes have made some contributions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure a–c presents the distributions of carbon atom numbers in the molecular formula assignments. The majority of the CHOS and CHONS species have carbon atom numbers of C 4 –C 11 , which can be derived from a variety of biogenic precursors and anthropogenic aromatic hydrocarbons and long-chain alkanes. , The species with C 8 –C 10 were particularly predominant, which might be associated with the oxidation products of benzene, polycyclic aromatic hydrocarbons, long-chain alkanes, and monoterpenes . The number of the CHOS species with C 12 –C 19 was apparently increased during the haze episode, suggesting that the precursors such as long-chain alkanes and/or sesquiterpenes have made some contributions.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum number of molecular formula candidates for each peak was set to 40. The molecular formula assignments in the two modes were performed using the elements of 12 C, 1 H, 16 O, 14 N, and 32 S, with the atom number constrained to the ranges of 1−50, 0−200, 0−50, 0−5, and 0− 2, respectively. 26−28 An additional 23 Na (atom number 0−1) was also used in positive mode for possible sodium adducts.…”
Section: Aerosol Sampling and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The double-bond equivalence (DBE) indicates the number of rings and double bonds in the molecules. DBE is calculated by the following equation ( Jiang et al, 2022 ). The aromaticity equivalent (X C ) is a more sensitive way to identify the aromatic and condensed aromatic rings possessing long alkyl chains, which was obtained using the equation: X C = [3(DBE − (p × o + q × s)) − 2] / [DBE − (p × o + q × s)], where p and q, respectively, denote the fraction of oxygen and sulfur atoms involved in the π-bond structure of a compound ( Yassine et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Organosulfur compounds have been found to be ubiquitous in atmospheric aerosols and can potentially play a role in determining aerosol physicochemical properties such as water uptake, viscosity, acidity, morphology and phase state. Sulfonate is an important class of organosulfur compounds in atmospheric aerosols. For instance, methanesulfonic acid (CH 3 SO 3 H, MSA) is known to be abundant in marine aerosols, which can be formed through aqueous-phase or gas-phase oxidation of dimethyl sulfide (DMS). Hydroxymethanesulfonate (CH 2 (OH)­SO 3 – , HMS) was also found to be present in atmospheric aerosols (Table S1) with concentrations ranging from 0.002 μg/m 3 in clean regions to 7 μg/m 3 in polluted environments. Atmospheric model simulations have also suggested that HMS can account for 10% of global aerosol sulfur in continental surface air and over 25% in most of urban polluted areas during winter. , …”
Section: Introductionmentioning
confidence: 99%